P. du Besset & D. Lyon : Logements à Gagny, France (1999)
Conjunto habitacional donde predomina el uso de espacios colectivos
Keywords: GAYNY; FRANCIA; CONJUNTOS HABITACIONALES; DU BESSET, PIERRE; LYON, DOMINIQUE